Human development, corruption control, and foreign direct investment revisited: the case of sub-Saharan Africa - Joseph Asante Darkwah; David Boohene; Cephas Paa Kwasi Coffie; Amma Addae-Nketiah; Amita Maxwell; Jacob Owusu Sarfo (Journal of Enterprise and Development (JED), 2023)
Purpose — This paper mainly studies how human development (value-added per worker) and control of corruption (CRPT) impact FDI inflows in sub-Saharan Africa. It also highlights the contributions of gross domestic product (GDP), inflation, population growth, natural resources, and political stability to foreign direct investment (FDI) inflows into sub-Saharan Africa (SSA).Method — The study employs the dynamic panel GMM model to estimate the factors that influence the region's foreign direct investment (FDI). The data span for the research was 33 years (1984 -2016).Result — The survey shows a strong connection between FDI inflow, human development, and corruption control. While human development has a beneficial influence, controlling corruption has an uncomplimentary impact on the growth of FDI in SSA.Contribution — There is a gap concerning human development and corruption control in SSA and how they impact FDI inflows. Researchers have attempted to establish this relationship, but they have mostly opted for individual countries and not predominantly in the Sub-Saharan region. This study contributes to the literature by concentrating on these variables (value added per worker and control of corruption) and how they interact with FDI inflows in the Sub-Saharan region.